Arteriovenous Fistula Anastomosis Diameter Association with the Ischemic Steal Syndrome Occurrence - Alsaadi, Mohammed J. (Open Access Macedonian Journal of Medical Sciences, 2022)
OBJECTIVE: Symptomatic Steal syndrome is one of the major complications following arteriovenous access fistula (AVF). The aim of this study is to investigate the association between AVF anastomosis diameter and the incidence of symptomatic steal syndrome. METHODS: A total of 103 patients with AVF were enrolled retrospectively in the study. There were two groups in the study, 77 patients with clinical symptomatic steal syndrome and 26 control with mature AVF with no symptoms. Anastomosis diameter was measured at the site of anastomosis and recorded at different fistula locations. Patient demographic, risk factors and access characteristics were recorded. RESULTS: Symptomatic Steal syndrome was more common among female patients (75.4%). Symptomatic Steal syndrome was more prevalent in patients with diabetes mellitus (DM), 77.8%, p<0.001. The mean anastomosis diameter in patients with Symptomatic steal syndrome was 3.74(±1.47) mm and in the control group 4.07(±1.79) mm, which indicates no significant difference in the anastomosis diameter, p=0.425. Analysis of covariance (ANCOVA) indicated that cardiovascular disease [F (1,94) =15.691, p=0.008] and peripheral vascular diseases [F (1,94) =13.059, p=0.016] are associated with steal syndrome incidence. CONCLUSION: The findings of this study conclude that there is no significant association between increased anastomosis diameter and the incidence of AVF steal syndrome.